Analysis of the Crime of Sexual Intercourse Committed by Minors (Case Study of Verdict Number 25/PID.SUS-ANAK/2023/PN.KOT) - Dinda Chairunissa Utomo (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
As regulated by Law Number 11 of 2012, juvenile offenders who commit the crime of intercourse with minors are still subject to legal proceedings, which begin with investigation, prosecution, and court examination using the juvenile criminal justice system. This research aims to determine whether the judge's considerations in sentencing the juvenile in case number 25/Pid.Sus-Anak/2023/PN.Kot are in accordance with the applicable laws. This normative juridical research emphasizes library research. This means studying and investigating primary and secondary legal sources obtained from legal materials or sources used in legal research. The research method applied is descriptive, aiming to describe the conditions or phenomena at a specific location and time. The legal sources used include primary and secondary legal materials. Based on the author's research, the considerations of the panel of judges in case number 25/Pid.Sus-Anak/2023/PN.Kot are in accordance with the applicable laws. The panel of judges has also taken into account the verdict through juridical, sociological, and philosophical aspects.